Acoustic-driven delta rhythms as prosodic markers. Issue 5 (28th May 2017) - Ghitza, Oded
ABSTRACT: Oscillation-based models of speech perception postulate a cortical computation principle by which decoding is performed within a time-varying window structure, synchronised with the input on multiple time scales. The windows are generated by a segmentation process, implemented by a cascade of oscillators. This paper tests the hypothesis that prosodic segmentation is driven by a "flexible" (in contrast to autonomous, "rigid") oscillator in the delta range (0.5–3 Hz) by tracking prosodic rhythms, such that intelligibility is impaired when the ability of this oscillator to synchronise to these rhythms is impaired. In setting phrasal boundaries, both bottom-up acoustic-driven and top-down context-invoked processes interact in a manner that is difficult to decompose. The present experiments used context-free random-digit strings in order to focus exclusively on bottom-up processes. Two experiments are reported. Listeners performed a target identification task, listening to stimuli with prescribed chunking patterns (Experiment I) or chunking rates (Experiment II), followed by a target. Irrespective of the chunking pattern, performance is high only for targets inside of a chunk, pointing to the benefit of acoustic prosodic segmentation in digit retrieval. Importantly, performance remains high as long as the chunking rate is within the frequency range of neuronal delta, but sharply deteriorates for higher rates. This data provides psychophysical evidence for the role of acoustic-driven segmentation, with flexible delta oscillations at the core, in digit retrieval.